2015
DOI: 10.19154/njwls.v5i4.4842
|View full text |Cite
|
Sign up to set email alerts
|

The Cabin Crew Blues. Middle-aged Cabin Attendants and Their Working Conditions

Abstract: This article examines how an airline company uses the labor of a group of middle

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Despite these limitations, the study findings contribute to an increased understanding of the causes and consequences of cabin crew fatigue. Many of the key factors contributing to cabin crew fatigue that were identified in the present study have been reported previously 1,3,5,6,9,42,43) . However, unlike previous studies, cabin crew in this study all had experience with ULR flights, for which FRMS processes were put in place by the airline to manage the associated fatigue risk.…”
Section: Study Limitationssupporting
confidence: 72%
See 1 more Smart Citation
“…Despite these limitations, the study findings contribute to an increased understanding of the causes and consequences of cabin crew fatigue. Many of the key factors contributing to cabin crew fatigue that were identified in the present study have been reported previously 1,3,5,6,9,42,43) . However, unlike previous studies, cabin crew in this study all had experience with ULR flights, for which FRMS processes were put in place by the airline to manage the associated fatigue risk.…”
Section: Study Limitationssupporting
confidence: 72%
“…While the physiological causes of fatigue are sleep loss and circadian disruption 2) , participants also identified a range of additional contributing factors at work and outside of work, including: insufficient rest, high workload, the work environment, a lack of company support and Industrial Health 2020, 58, 2-14 insufficient fatigue management training. Most of these factors have been identified previously 1,3,5,6,9,42,43) . However, the present study also highlights the importance of sufficient rest not only for obtaining adequate recovery sleep but also for achieving a work-life balance.…”
Section: Discussionmentioning
confidence: 97%
“…First, contemporary human service employees (flight attendant) may perceive certain kind of role ambiguity in the changing industrial climate, even though they clearly understand their roles; the main tasks for flight attendants are security, safety and customer service with hospitality. An explanation may be that the contemporary aviation is no longer only a luxury experience for the privileged few customers and has become a mass transportation with other characteristics turning to a passenger group that is more heterogeneous, including business people, casual travelers, holidaymarkers, and commuters with other requirements [28]. Therefore, the presentation of the customer service of flight attendants has gradually changed, for example, the service should be rapid for more passengers.…”
Section: Discussion and Implicationmentioning
confidence: 99%
“…Therefore, there are many dimensions of climate (e.g., safety, service, or innovation) [21]. In the recent airline industry, there is an ongoing trend (or climate) to employ as few people as possible to do as much possible [28]. Another trend is increasing demands of employee flexibility to meet variations in the employee's needs and growing job insecurity [28].…”
Section: Organizational Climatementioning
confidence: 99%
See 1 more Smart Citation